ANALISIS KOMPONEN KIMIA AKTIF ISOLAT DAUN Colocacia esculenta L. IDTK01 SECARA SPEKTROFOTOMETER INRA MERAH - Herwin, Herwin; Baits, Muzakkir; Ririn, Ririn; Harly Nurung, Ayyub (Jurnal Ilmiah As-Syifaa, 2021)
The objective of this research is to analysis chemical coumpounds active isolate of Colocacia esculenta L.’s leaves IDTK01 using infra red spectrophotometer. The fractionation of the ethanolic extract of Colocasia esculenta L’s leaves using liquid vacuum chromatography obtained 7 fractions. Active fraction was B fraction isolated from the active coumpound by TLC-preparative from 3 different isolate, IDTK01, IDTK02 dan IDTK03. IDTK01 isolate was tested its antibacterial activity using TLC-bioautography with eluen n-hexane:ethyl acetate (10:1) and its active against Salmonella thypi with Rf value 0.98. Active isolate IDTK01 was analyze its active bacterial coumpound using infrared spectrophotometer and the results is hydrogen bond, hydroxyl functional group (OH), aryl/ aromatic (C=C), aliphatic (CH2), Ether aldehyde (C-O), and pyridine.